(untitled) (Journal of the Bangladesh Agricultural University, 2020)
Country bean is a nutritious vegetable with commercial importance. Pod borer is a major pest of country beans in Bangladesh. Assessment of genetic variation among germplasm is a prerequisite for improvement of any crop. The present study was conducted to evaluate the yield potential, pod borer resistance and genetic diversity of 20 country bean varieties. At first, a field experiment was conducted with twenty cultivars to evaluate yield contributing characters and pod borer resistance. The data revealed that the variety Kaloputi showed the highest yield (2111.09 g) of pods plant–1. This variety (Kaloputi) had the highest number of pods plant–1 (271), lowest percentage (3.08%) of infestation, highest number (1086.0) of seeds plant–1 and highest dry seed yield over the other varieties. The variety BARI seem 5 showed the least performance in most of the parameters. Another experiment was conducted to find the genetic diversity among the 20 cultivars using SSR markers. The cluster analysis showed that the genotypes were divided into four groups. The cluster 1 was composed of seven BARI released varieties, cluster 2 was composed of two modern (IPSA seem 2 and BARI seem 8) and three local varieties (Khisamoti, Rifa and Goalgada), cluster 3 was constructed by six local and one modern variety (BARI seem 9) and Cluster 4 consisted of only cultivar Mostofa. The wide variations in phenotypic and genotypic level and pod borer resistance observed among the genotypes can be potentially used for future improvement of country bean. J Bangladesh Agril Univ 18(1): 25–33, 2020 https://doi.org/10.5455/JBAU.73722